Auditoría en seguridad vial en los tramos: Variante la Paz, Chinchiná la Ye, la Ye la Trinidad (2021)
The work carried out on carrying out a Road Safety Audit to the variables: barriers, geometric design of the road and signaling, to establish its condition in front of the road actors that circulate on it, in the section included, from the beginning of the section the variant La Paz to the Chinchiná roundabout the route is the 29 RSC, to the La Y site, until the Trinidad intersection, route 29CL03 - 1, another from the Chinchiná roundabout to the La Ye site where the road forks towards Manizales and Medellín ruta 29CL03, was fulfilled in its entirety and the realization of each one of the specific objectives was carried out, for this a bibliographic investigation of the works at international, national and local level that had as objective the accomplishment of Audits or that were carried out models (manuals) for its realization, likewise a bibliography compilation of the theoretical references was made in order to understand the Genesis and structure of the ASV, the methodology for e The development of the project corresponded to the quantitative descriptive one, the variables used for each objective were characterized, the methods were submitted and the results found were described for with this information, an analysis of the results found was carried out through presents a moderately tolerable risk, for which It is recommended to carry out: a physical intervention to the infrastructure, analysis of operational, control and corrective policies and strengthen by improving logistics on road education focused on the most vulnerable actors.